Seismic fragility analysis of pile supported wharf using linear time history analysis - Shah, Dhara; Shah, B.J. (Journal of Structural Engineering, 2024)
Ports and harbors are considered as lifeline structures because of the significant role they play in transporting people and cargos cost effectively. Currently in India, no guideline is available for seismic design of Port structures and hence vulnerability analysis of such structures becomes essential. Seismic fragility analysis, in terms of fragility curves; represent the probability that the structural damage of a structure, under various levels of seismic ground motions, exceed specified damage states. In present study, seismic fragility curves are developed for an existing pile supported wharf at Mundra port, Gujarat, India. The selected site is in seismic zone V with MCE as 0.36g (IS:1893 part-I, 2002). SAP 2000 is used to create structural model of wharf along with Winkler model to represent soil pile system, in which the pile and soil is symbolized by beam elements and springs respectively. Pushover analysis is performed on the model to find the capacity of wharf. Damage states – serviceable, repairable, near collapse and collapse; are established as per PIANC (PIANC, 2001). Site specific spectra is created using geotechnical report along with ASCE7-05 and correspondingly 10 seismic events are selected, normalized and scaled to 0.1g,0.2g,…1.0g to represent demand. Using linear time history analysis, maximum displacements at deck are obtained and response matrix is created. Based on the damage states and the response matrix, the fragility curves of the wharf are constructed with statistical analysis, using Microsoft Excel. It is revealed that the variation in PGA for DBE, at selected site, as per ASCE7-05(0.883g) and IS: 1893-2002 (0.18g), is nearly 400 % with respect to IS: 1893-2002, which demands the need for revision in the available standards. As per IS: 1893-2002 for MCE(0.36g), the probability of structure entering into repairable, near collapse and collapse state is 100%, 18% and 5% whereas PGA obtained at site for MCE (1.325g), states the probability as 100% for all states, which demands retrofitting the structure to resist future earthquakes.